The interaction of 4-hydroxymethyl isoindolines with dehydrobenzene. Synthesis of 3-phenylaminomethyldihydrobenzo[c]furanes. Issue 8 (25th February 2015) - Varlamov, Alexey V.; Guranova, Natalia I.; Borisova, Tatiana N.; Toze, Flavien A.A.; Ovcharov, Maxim V.; Kristancho, Sindi; Voskressensky, Leonid G.
Abstract: 2-Alkyl or 2-aryl-substituted 4-hydroxymethylisoindolines smoothly undergo intramolecular recyclization through reaction with arynes to give isobenzofurans with good yields. Graphical abstract: